Acupuncture Therapy plus Hyaluronic Acid Injection for Knee Osteoarthritis: A Meta-Analysis of Randomized Controlled Trials. (13th January 2020) - Zheng, Yang; Duan, Xiangdong; Qi, Shangfeng; Hu, Haibo; Wang, Mengran; Ren, Conglin; Xu, Haipeng; Quan, Renfu
Abstract : Objective . This meta-analysis aimed to investigate the effectiveness of acupuncture therapy plus hyaluronic acid injection versus hyaluronic acid injection alone for patients with knee osteoarthritis. Methods . Relevant randomized controlled trials that compared the combined effect of acupuncture therapy and hyaluronic acid injection with hyaluronic acid injection alone for knee osteoarthritis patients were included. 10 studies were included in this meta-analysis, and the relative risk (RR) and weight mean difference (MD) with 95% CI for the Lysholm knee score (LKSS), visual analogue scale (VAS), and effective rate (ER) were evaluated by using RevMan 5.3 software. Besides, the bias assessment of the included studies was evaluated using the Cochrane risk of bias tool, and the GRADE (Grading of Recommendations, Assessment Development, and Evaluation) system was applied to assess the overall quality of the evidence. Results . A total of 10 studies involving 998 participants were included in this study. Compared to hyaluronic acid injection alone, the combined therapy significantly reduced pain on the visual analogue scale (VAS) and improved the ER and knee function on the Lysholm knee score (LKSS). Of these, the pooled LKSS (MD = 8.09, 95% CI = [7.02, 9.16], p < 0.00001, 7 studies) and ER (RR = 1.23, 95% CI 1.15 to 1.31, p < 0.00001, 8 studies) suggested that combination therapy yielded a significantly higher ER and improved the LKSS scores to a greater degree than hyaluronic acid injection alone in patients with KOA. The VAS (MD = −1.39, 95% CI = [−1.99, −0.79], p < 0.00001, 7 studies) showed that the combined therapy significantly reduced pain than hyaluronic acid injection alone. The quality of evidence for the main outcomes was from very low to low according to the GRADE system. Conclusion . Current evidence suggests that acupuncture therapy combined with hyaluronic acid injection is more effective in alleviating pain, improving the ER and knee function compared with hyaluronic acid injection alone. However, considering the low quality, small size, and high risk of the studies identified in this meta-analysis, more higher methodological quality, rigorously designed randomized controlled trials with large sample sizes are needed to confirm the results.